2021
DOI: 10.1002/chem.202102208
|View full text |Cite|
|
Sign up to set email alerts
|

NIR‐Emissive Chromium(0), Molybdenum(0), and Tungsten(0) Complexes in the Solid State at Room Temperature

Abstract: The development of NIR emitters based on earthabundant elements is an important goal in contemporary science. We present here Cr(0), Mo(0), and W(0) carbonyl complexes with a pyridyl-mesoionic carbene (MIC) based ligand. A detailed photophysical investigation shows that all the complexes exhibit dual emissions in the VIS and in the NIR region. The emissive excited states are assigned to two distinct triplet states by time-resolved emission and step-scan FTIR spectroscopy at variable temperature, supported by d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 79 publications
3
59
0
Order By: Relevance
“… 97 More recently, the same groups have shown that the aforementioned Cr(0) and Mo(0) and the analogous W(0) complexes are dual emitters in the solid state at room temperatures. 153 These complexes emit in the visible as well as in the NIR II region. The quantum yield, particularly for the W(0) complex, is remarkably high.…”
Section: Redox Photochemical/photophysical Properties Of Metal Complexesmentioning
confidence: 99%
“… 97 More recently, the same groups have shown that the aforementioned Cr(0) and Mo(0) and the analogous W(0) complexes are dual emitters in the solid state at room temperatures. 153 These complexes emit in the visible as well as in the NIR II region. The quantum yield, particularly for the W(0) complex, is remarkably high.…”
Section: Redox Photochemical/photophysical Properties Of Metal Complexesmentioning
confidence: 99%
“…platinum, ruthenium, iridium, or lanthanide ions [5] . Over the past years, growing efforts have been dedicated to develop and exploit new types of photoactive metal complexes based on earth‐abundant metals, such as copper, [6] zirconium, [7] iron, [8] molybdenum, [9] manganese, [10] cobalt, [11] and chromium, [9d,12] which are considered as promising candidates for eco‐friendly luminescence and photocatalysis applications [13]…”
Section: Introductionmentioning
confidence: 99%
“…Mesoionic carbenes (MICs) have recently attracted a lot of attention in the field of transition‐metal catalysis for organic transformations [1–9] and photophysical materials [10–16] . In particular, 1,2,3‐triazol‐5‐ylidene (triazolylidene) is the most attractive ligand motif and has been well established because it can be easily synthesized via the [3+2] Huisgen reaction between alkynes and azides [17–18] .…”
Section: Introductionmentioning
confidence: 99%
“…Mesoionic carbenes (MICs) have recently attracted a lot of attention in the field of transition-metal catalysis for organic transformations [1][2][3][4][5][6][7][8][9] and photophysical materials. [10][11][12][13][14][15][16] In particular, 1,2,3-triazol-5-ylidene (triazolylidene) is the most attractive ligand motif and has been well established because it can be easily synthesized via the [3 + 2] Huisgen reaction between alkynes and azides. [17][18] Although several reports have been published on the palladium chemistry of MIC complexes, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] examples of MICs bound to nickel centers are rare, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation